2013
DOI: 10.1111/scs.12048
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' experiences of feeding babies born with cleft lip and palate

Abstract: Cleft lip and palate (CLP) in newborns have implications for feeding. It might impede the child's attempts to seal around the nipple and to create intraoral pressure. Parents needed support and information about feeding after birth. Mothers' own experiences and how they coped with the challenges related to feeding have not been extensively studied. The aims of this study were twofold: to describe the experiences of feeding for mothers of children born with CLP and to elucidate how the mothers cope with the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
83
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(95 citation statements)
references
References 26 publications
8
83
0
4
Order By: Relevance
“…In such situations, mothers have reported receiving little or no support, being given inaccurate advice and being discouraged from even trying to breastfeed by the non-specialist health care professionals who are present (Bessell et al, 2010). This is likely to result in added stress, confusion, uncertainty and anxiety for parents and health professionals at a time that is already difficult (Lindberg & Berglund, 2011) …”
Section: Post-natal Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…In such situations, mothers have reported receiving little or no support, being given inaccurate advice and being discouraged from even trying to breastfeed by the non-specialist health care professionals who are present (Bessell et al, 2010). This is likely to result in added stress, confusion, uncertainty and anxiety for parents and health professionals at a time that is already difficult (Lindberg & Berglund, 2011) …”
Section: Post-natal Supportmentioning
confidence: 99%
“…Breastfeeding support is an integral part of post-natal care for all mothers and should comprise appropriate advice, support and encouragement (Beaumont, 2012;Lindberg & Berglund, 2011). Unfortunately this is not always provided and parents of children born with a cleft have, historically, expressed dissatisfaction with the way that breastfeeding support and information is provided, often because staff lack knowledge and expertise (Nelson et While the CNS are trained to assess the infant's oral skills after birth and provide advice about appropriate and effective feeding methods, they may not always be able to attend in the immediate period after the birth (Beaumont, 2012).…”
Section: Post-natal Supportmentioning
confidence: 99%
“…First, a cleft of the palate impedes the creation of negative intraoral pressure during sucking [8], preventing nutritive sucking [9] and probably also reducing non-nutritive sucking acts such as pacifier use [2]. Second, surgeries in the orofacial area are frequently performed in the early stages of life (e.g., lip closure, palatal closure etc.).…”
Section: Introductionmentioning
confidence: 99%
“…As for breastfeeding 90% of mothers demanded demonstration. In a study by Young et al (2001) reported that 40% of the parents were not instructed to how to face such feeding difficulties and 55% were giving a brief information on feeding interventions 18,19,20 . In the present study, out of the 37 infants with prenatal cleft diagnosis, 91.9%(n=34) parents had investigated the methods that they can feed their infants with, and 46% (n=17) were educated before the birth of their child.…”
Section: Discussionmentioning
confidence: 99%
“…Shall they ask for professional take-care giver help and support? 6 .There is dearth of data regarding studies focusing on feeding problems and approaches to be developed to compensate for such difficulty with (CLP) infants. Feeding difficulty or feeding skills as described by different authors, occurs in a range of one third to a maximum of two thirds of the infants 7,8 .…”
Section: Introductionmentioning
confidence: 99%